Manganese-catalyzed cyclopropanation of allylic alcohols with sulfones - Yu, Ke; Nie, Qin; Chen, Qianjin; Liu, Weiping (Nature communications, 2024)
Cyclopropanes are among the most important structural units in natural products, pharmaceuticals, and agrochemicals. Herein, we report a manganese-catalyzed cyclopropanation of allylic alcohols with sulfones as carbene alternative precursors via a borrowing hydrogen strategy under mild conditions. Various allylic alcohols and arylmethyl trifluoromethyl sulfones work efficiently in this borrowing hydrogen transformation and thereby deliver the corresponding cyclopropylmethanol products in 58% to 99% yields. Importantly, a major benefit of this transformation is that the versatile free alcohol moiety is retained in the resultant products, which can undergo a wide range of downstream transformations to provide access to a series of functional molecules. Mechanistic studies support a sequential reaction mechanism that involves catalytic dehydrogenation, Michael addition, cyclization, and catalytic hydrogenation. Developing readily available and bench-stable reagents for the cyclopropanation of olefins is needed as traditional methodologies mainly rely on carbene-based strategies. Herein, the authors report a manganese-catalyzed cyclopropanation of allylic alcohols with sulfones via a borrowing hydrogen strategy under mild conditions.